Debating childhood masculinities : rethinking the interplay of age, gender and social change - Mukherjee, Utsa (Emerald advances in masculinities, 2024)
Foregrounding children's agency and voices, Debating Childhood Masculinities brings together cutting-edge interdisciplinary scholarship to examine how childhood masculinities are constructed, experienced and regulated in different parts of the world. Adopting a gender-inclusive approach, authors in this edited collection embrace a variety of anti-racist, feminist, neomaterialist and queer frameworks to showcase an international and interdisciplinary body of scholarship that explores the way childhood masculinities in today's world are being negotiated and lived out in the context of wider social change across gender relations and masculine ideals. Grounded in the premise that childhood masculinities are not biologically determined, chapters outline how children's understanding and enactment of masculinity are culturally conditioned, historically contingent, social-material constructions that are produced at the intersection of generational and gendered relations. Providing an impactful and ground-breaking contribution to the fields of childhood and masculinity studies, this expert collection leads the academic conversation on masculinities into new and productive directions. The fresh insights offered here will be useful to childhood practitioners, educators and policy makers who are committed to gender equity and democratisation.